2019
DOI: 10.1177/1758155919832190
|View full text |Cite
|
Sign up to set email alerts
|

Could gaps and diverse topography compensate for habitat deficiency by the forest-dwelling bird Hazel Grouse (Tetrastes bonasia)?

Abstract: The Hazel Grouse ( Tetrastes bonasia) is considered an indicator of the naturalness and heterogeneity of the forest environment. This species occurs in various woods and forages on a variety of plants. The aim of this study was to verify the hypothesis that, in Norway spruce-dominated forest stands, the Hazel Grouse compensates for habitat poverty using non-forest areas and harsh topography, which deliver food resources and shelter for the birds. We compared 14 environmental and topographic variables in forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Kortmann et al (2018) showed that decreasing canopy cover increased the probability of hazel grouse presence in the Bavarian Forest (SE Germany). Moreover, we found the presence of open areas as overgrown glades was an important factor for hazel grouse occurrence in mixed mountain forests, similar as in high-mountain spruce forests (Matysek et al 2019). Adra et al (2013) showed that small forest openings are essential for this species in the French Alps.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Kortmann et al (2018) showed that decreasing canopy cover increased the probability of hazel grouse presence in the Bavarian Forest (SE Germany). Moreover, we found the presence of open areas as overgrown glades was an important factor for hazel grouse occurrence in mixed mountain forests, similar as in high-mountain spruce forests (Matysek et al 2019). Adra et al (2013) showed that small forest openings are essential for this species in the French Alps.…”
Section: Discussionmentioning
confidence: 52%
“…Hazel grouse habitat requirements are relatively well known in boreal and mountain ecosystems covered by coniferous forests (Bergmann et al 1996;Kämpfer-Lauenstein 1997;Åberg et al 2003;Mathys et al 2006;Müller et al 2009;Schäublin and Bollman 2011;Ludwig and Klaus 2017), and less known in mixed or deciduous forests (Wiesner et al 1977;Rhim 2006;Kajtoch et al 2012;Matysek et al 2018Matysek et al , 2019. Habitat preferences differ in detail according to diversity of available sites.…”
Section: Introductionmentioning
confidence: 99%
“…Striking however, was the strong negative response of Siberian Grouse to increasing proportions of pioneer trees. In European studies, pioneer trees was shown to be an important winter food and crucial habitat element for the Hazel Grouse (Bergmann et al 1996, Klaus 1996, Matysek et al 2019, Müller et al 2009a, Salo 1971, Schäublin & Bollmann 2011, Swenson 1993. Also, in South Korea, Hazel Grouse prefers forests rich in pioneer trees (Rhim 2013).…”
Section: Sympatric Occurrencementioning
confidence: 99%
“…This species occurs in both lowlands and mountainous regions across Eurasia inhabiting coniferous and mixed forests (Cramp & Simmons 1980, Johnsgard 1983, Bergmann et al 1996. The Hazel Grouse is a territorial bird with specific habitat and food requirements (e.g., Bergmann et al 1996, Bonczar et al 1998, Swenson 2006, Matysek et al 2018, Matysek et al 2019a). The species maintains a territory throughout the year, staying in one place (e.g., Swenson 1991a, Swenson 1991b, Montadert & Leonard 2006.…”
Section: Introductionmentioning
confidence: 99%